Guru SD Sebagai “Model” Dalam Meningkatkan Indigeneousasi Pada Siswa Sekolah Dasar - Anak Agung Putu Sugiantiningsih; Yossita Wisman; Cukei (FKIP Universitas Palangka Raya, 2023)
Formal education in Indonesia starts from elementary school level. In elementary school, students experience development in the personal-social (personal-social development), academic (academic development) and career (career development) aspects, so that they become a generation of a nation that is independent and actively develops its potential, has religious spiritual strength, self-control, personality, intelligence, noble character, and skills needed by himself, society, nation and state. The development of elementary school students, apart from their families, is influenced by the school/educational environment. For example, elementary school students are very obedient to what their teachers say, because elementary school teachers, for them, are figures they